Germline and Somatic Pharmacogenomics to Refine Rectal Cancer Patients Selection for Neo-Adjuvant Chemoradiotherapy - De Mattia, Elena; Roncato, Rossana; Palazzari, Elisa; Toffoli, Giuseppe; Cecchin, Erika (Frontiers in Pharmacology, 2020)
Neoadjuvant chemoradiation (nCRT) followed by radical surgery is the standard of care for patients with Locally Advanced Rectal Cancer (LARC). Current selection for nCRT is based on clinical criteria regardless of any molecular marker. Pharmacogenomics may be a useful strategy to personalize and optimize nCRT in LARC. This review aims to summarize the most recent and relevant findings about the role of germline and somatic pharmacogenomics in the prediction of nCRT outcome in patients with LARC, discussing the state of the art of their application in the clinical practice. A systematic literature search of the PubMed database was completed to identify relevant English-language papers published up to January 2020. The chemotherapeutic backbone of nCRT is represented by fluoropyrimidines, mainly metabolized by DPD (Dihydro-Pyrimidine Dehydrogenase, DPYD). The clinical impact of testing DPYD*2A, DPYD*13, c.2846A>T and c.1236G>A-HapB3 before a fluoropyrimidines administration to increase treatment safety is widely acknowledged. Other relevant target genes are TYMS (Thymidylate Synthase) and MTHFR (Methylene-Tetrahydro-Folate Reductase), whose polymorphisms were mainly studied as potential markers of treatment efficacy in LARC. A pivotal role of a TYMS polymorphism in the gene promoter region (rs34743033) was reported and was pioneeringly used to guide nCRT treatment in a phase II study. The pharmacogenomic analysis of other pathways mostly involved in the cellular response to radiation damage, as the DNA repair and the activation of the inflammatory cascade, provided less consistent results. A high rate of somatic mutation in genes belonging to PI3K (Phosphatidyl-Inositol 3-Kinase) and MAPK (Mitogen-Activated Protein Kinase) pathways, as BRAF (V-raf murine sarcoma viral oncogene homolog B1), KRAS (Kirsten Rat Sarcoma viral oncogene homolog), NRAS (Neuroblastoma RAS viral (v-ras) oncogene homolog), PIK3CA (Phosphatidyl-Inositol-4,5-bisphosphate 3-Kinase, Catalytic Subunit Alpha), as well as TP53 (Tumor Protein 53) was reported in LARC. Their pharmacogenomic role, already defined in colorectal cancer, is under investigation in LARC with promising results concerning specific somatic mutations in KRAS and TP53, as predictors of tumor response and prognosis. The availability of circulating tumor DNA in plasma may also represent an opportunity to monitor somatic mutations in course of therapy.